Robert Musil. La guerra nelle parole: tra sogno, redenzione e “altro stato”: [Robert Musil. The War in his Words: through Dream, Redemption and “the Other Condition”] (Studia austriaca, 2018)
Through a close examination of The Man without Qualities, some of the writings contained in The Literary Nachlass and especially The Redeemer, one of the most significant preliminary versions of the novel, the article shows the evolution of Musil’s thought about the First World War. He supported it initially, as did many European intellectuals. However, in retrospect and in the fine weave of the words used in the materials mentioned above, Musil ends up seeing in the Great Conflict only the failure of a “buried humanity”.